22.0k views
1 vote
I need help for question 19 !!!!! I also need to explain my answer.. PLEASEEEEEE

I need help for question 19 !!!!! I also need to explain my answer.. PLEASEEEEEE-example-1

1 Answer

4 votes

The value of m is 3.

Solution:

Given equation:

6 + 5(m + 1) = 26

To solve the equation:

6 + 5(m + 1) = 26

Multiply 5 into each term inside the bracket.

6 + 5m + 5 = 26

5m + 11 = 26

Subtract 11 on both sides, we get

5m = 15

Divide by 5 on both sides, we get

m = 3

The value of m is 3.

Checking:

6 + 5(m + 1) = 6 + 5(3 + 1)

= 6 + 5(4)

= 6 + 20

= 26

6 + 5(m + 1) = 26.

Hence the solution is correct.

User Sam Boosalis
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.